Metal copper catalyst as well as preparation method and application thereof
By growing copper catalysts by electrodeposition on carbon paper support, a high-density (110) crystal surface is formed, and the problem of low selectivity for conversion of CO2 into ethanol products in the prior art is solved, and efficient and stable ethanol generation is achieved.
Patent Information
- Application Number
- CN202411903502.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
When the prior art uses an electrocatalyst to convert CO2 into ethanol, the product selectivity is low and there are many by-products, making it difficult to achieve industrial application.
By modifying and activating carbon paper hydrophilicity, a mixture of copper nitrate, sulfuric acid, citric acid and water was used as an electrolyte, and a copper catalyst was grown on the carbon paper support by electrodeposition method to form high-density (110) crystals with high density (110) metal copper catalyst on the surface.
The yield of ethanol products was significantly improved, with the Faraday efficiency reaching a maximum of 78.9%, and the impact of organic capping agents on the catalytic process was avoided, thereby improving the stability and selectivity of the catalyst.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysts, and in particular relates to a metallic copper catalyst and a preparation method and application thereof. Background Art
[0002] The excessive use of fossil energy has caused the concentration of CO2 in the atmosphere to rise year by year, which has brought about a series of environmental problems. Taking effective measures to curb CO2 emissions and promote effective carbon cycles are of great significance to help achieve the "dual carbon" goals. Electrocatalytic technology can convert CO2 into high-value-added chemicals, realize its resource utilization, promote carbon cycles, and reduce carbon emissions. Among them, ethanol, as one of the reduction products of CO2, has important medical and industrial application value. However, due to the complexity of the CO2 reduction reaction and the large number of by-products, the current use of this strategy to prepare ethanol is still a certain distance from industrial application. Therefore, the development of low-cost catalysts with high ethanol selectivity is a key step in promoting the effective conversion of CO2 to ethanol products.
[0003] Among many electrocatalysts, Cu is the only material that can simultaneously convert CO2 into C1 and C2 products. Among them, the crystal plane regulation of Cu shows high sensitivity to CO2 reduction products. A large number of studies have shown that the (111) crystal plane of Cu has a higher selectivity for methane products, while the (100) crystal plane has a higher selectivity for ethylene products. Ethanol products tend to be generated on the (110) step surface and some high-index crystal planes. However, in actual studies, it was found that the efficiency of ethanol production is much lower than the theoretical level. This is mainly due to two reasons: (1) The (110) crystal plane of Cu is located at the interface of the (100) and (111) crystal planes and cannot exist alone. It is difficult to obtain a large area of exposure of the (110) crystal plane in experiments, which limits the selectivity of ethanol products. (2) In conventional synthesis methods, organic capping agents are often added to the reaction system to induce the exposure of specific Cu crystal faces. However, incomplete removal of these organic substances will not only hinder the smooth transfer of charge on the catalyst surface, but also interfere with the CO2 reduction pathway and reduce product selectivity (ACS Catal. 2021, 11, 13330-13336; ACS Nano 2016, 10, 4559-4564; ACS Catal. 2019, 9, 7894-7899; J. Phys. Chem. Lett. 2019, 10, 4259-4265; Coord. Chem. Rev. 2022, 454, 214340).
[0004] A Chinese patent application with publication number CN 114134530 A discloses a method for preparing a Cu-P-100 catalyst and its application in the electrocatalytic reduction of carbon dioxide. The preparation method uses a mixed system of tannic acid and copper nitrate as an electrolyte to prepare a Cu catalyst. Although this method successfully avoids the use of an organic capping agent, the obtained catalyst does not show special crystal face exposure. In the CO2 reduction reaction, a mixed product containing multiple components such as carbon monoxide (CO), methane (CH4), formic acid (HCOOH), acetic acid (CH3COOH), etc. is generated, and there is no report on ethanol products. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a metallic copper catalyst and a preparation method and application thereof. The catalyst has a high-density (110) crystal face, which significantly improves the yield of ethanol products in the CO2 reduction reaction. At the same time, the catalyst avoids the influence of the use of an organic capping agent on the catalytic process.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a metallic copper catalyst comprises: S1, hydrophilic modification and activation of carbon paper to obtain a carbon paper carrier; S2, using a mixture of copper nitrate, sulfuric acid, citric acid and water as the electrolyte, the copper catalyst was grown on the carbon paper support by electrodeposition; S3, washing and drying the carbon paper carrier on which the copper catalyst is grown, to obtain a metallic copper catalyst supported on the carbon paper carrier.
[0007] Preferably, in the method for preparing the metallic copper catalyst, S1 specifically comprises: (1) The carbon paper is washed with deionized water and anhydrous ethanol to remove impurities, then added into a sulfuric acid solution and heated to obtain a hydrophilic carbon paper; (2) In a three-electrode system, sulfuric acid solution is used as the electrolyte and cyclic voltammetry is used to activate the hydrophilic carbon paper to obtain a carbon paper carrier.
[0008] Preferably, in step (1), the heating temperature is 50-70° C. and the heating time is 50-70 min.
[0009] Preferably, in step (2), the three-electrode system uses a Pt sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and a hydrophilic carbon paper as a working electrode, and the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -1.7 V to -2.3 V, the starting potential is 0 V, the number of cycles is 6 to 8 times, and the scanning speed is 90 to 110 mV / s.
[0010] Preferably, in the method for preparing the metallic copper catalyst, in S2, in the electrolyte, the concentration of copper nitrate is 0.005~0.05 mol / L, and the concentration of citric acid is 0.01~0.1 mol / L.
[0011] Preferably, in the method for preparing the metallic copper catalyst, in S2, the pH value of the electrolyte is 1-4.
[0012] Preferably, in the method for preparing the metallic copper catalyst, in S2, the electrodeposition time is 100 to 500 s.
[0013] Preferably, in the method for preparing the metallic copper catalyst, in S2, the potential applied by the electrodeposition method is -1.0~-1.4 V. The invention also provides a metallic copper catalyst obtained by adopting the preparation method.
[0014] The present invention also provides application of the metallic copper catalyst in electrocatalytic CO2 reduction.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the metal copper catalyst of the present invention adopts an electrolyte solution of a mixture of copper nitrate, sulfuric acid, citric acid and water. During the synthesis process, citric acid and copper nitrate form a stable complex. Compared with tannic acid, citric acid has a simpler chemical structure and smaller steric hindrance. Therefore, the complex formed by citric acid and copper nitrate is more inclined to self-assemble under the action of an external electric field, so that Cu atoms are arranged along a direction with lower energy; while the complex formed by tannic acid and copper nitrate cannot self-assemble due to the presence of large steric hindrance, and can only form nanoparticles without fixed crystal face exposure during the electrodeposition process. During the electrodeposition process, the energy of different Cu crystal faces is respectively Cu (111) 1.952 J m -2 <Cu(100)2.166 J m -2 <Cu(110)2.237 J m -2Therefore, in the present invention, the (111) crystal plane and the (100) crystal plane of Cu grow alternately along the Z axis, thereby forming a metallic copper catalyst with rich (110) crystal planes. During the electrocatalytic reduction of CO2, compared with the pure (100) crystal plane, a rapid CC coupling process can occur on the (110) crystal plane to promote the formation of C2 products. At the same time, compared with the (111) crystal plane, the removal process of H2O during the catalytic process on the (110) crystal plane is inhibited. Therefore, the selectivity of ethanol products on the (110) crystal plane is significantly improved. In addition, citric acid forms a stable complex with copper nitrate, which can also inhibit the deposition of copper nitrate and ensure the smooth progress of the electrodeposition process. The addition of sulfuric acid ensures good conductivity of the electrolyte. The catalyst of the present invention is obtained by a one-step electrodeposition method, which avoids the influence of the use of an organic capping agent on the catalytic process.
[0016] Furthermore, through appropriate regulation of the electrodeposition process, a metallic copper catalyst with a special hexagonal tower morphology can be obtained. The hexagonal tower-shaped metallic copper catalyst has a higher density of (110) crystal planes, which further improves the yield of ethanol products in the CO2 reduction reaction.
[0017] The metal copper catalyst of the present invention is mainly used in the electrocatalytic CO2 reduction system. In a specific embodiment of the present invention, at -0.21 vs Under the overpotential of RHE, the Faradaic efficiency of the metallic copper catalyst for ethanol products reached as high as 78.9%, which is a significant improvement compared to other Cu-based electrocatalysts, and showed good stability in the CO2 reduction test lasting up to 18 hours (6 cycles). BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The morphologies of (a) Cu-N-300, (b) Cu-C, and (c) CS catalysts. Figure 2 Morphology images of (a, b) Cu-N-100 and (c, d) Cu-N-500 catalysts; Figure 3 This is the atomic arrangement diagram of Cu-N-300 catalyst observed under a double spherical aberration corrected microscope; Figure 4 XRD patterns of Cu-N series catalysts and Cu-C and CS catalysts; Figure 5 It is the ratio diagram of different crystal surface contents in Cu-N series catalysts and Cu-C and CS catalysts; Figure 6 The morphology of the catalysts obtained under different synthesis conditions; Figure 7 The morphologies of the catalysts obtained by (a) electrodeposition on unactivated carbon paper, (b) on copper foil, and (c) using tannic acid as a complexing agent. Figure 8 Distribution diagram of electrocatalytic CO2 reduction products of (a) Cu-N-300, (b) Cu-C, and (c) CS catalysts at different overpotentials; Fig. 9 The electrocatalytic CO2 reduction product distribution diagram of the catalysts obtained in different embodiments and comparative examples at the optimal overpotential; Fig.10 This is the electrocatalytic CO2 reduction cycle stability test diagram of Cu-N-300 catalyst. DETAILED DESCRIPTION
[0020] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0021] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0022] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0023] The preparation method of the metal copper catalyst of the invention uses copper nitrate as a precursor and adopts a one-step electrodeposition method to grow the copper catalyst on the surface of hydrophilic carbon paper.
[0024] Specifically, the preparation method of the metallic copper catalyst of the present invention comprises: S1, hydrophilic modification and activation of carbon paper to obtain a carbon paper carrier; S2, using a mixture of copper nitrate, sulfuric acid, citric acid and water as the electrolyte, the copper catalyst was grown on the carbon paper support by electrodeposition; S3, washing and drying the carbon paper carrier on which the copper catalyst is grown, to obtain a metallic copper catalyst supported on the carbon paper carrier.
[0025] The preparation method of the metal copper catalyst of the present invention uses a mixed solution of copper nitrate, sulfuric acid, citric acid and water as an electrolyte and carbon paper as a carrier. The metal copper catalyst with abundant (110) crystal faces can be controllably grown on the carbon paper carrier by an electrodeposition method. Compared with the (111) crystal face, the removal process of H2O in the catalytic process on the (110) crystal face in the CO2 reduction reaction is suppressed, so the selectivity of the ethanol product on the (110) crystal face is significantly improved.
[0026] The specific preparation method of the carbon paper carrier described in S1 of the present invention comprises the following steps: (1) The carbon paper is washed with deionized water and anhydrous ethanol to remove impurities, then added to a sulfuric acid solution and heated to obtain a hydrophilic carbon paper.
[0027] Specifically: the cleaning method used for cleaning carbon paper is ultrasonic cleaning, and the ultrasonic time is 8~12 min; the concentration of sulfuric acid solution is 0.9~1.1 mol / L, the heating temperature is 50~70℃, and the heating time is 50~70 min.
[0028] (2) In a three-electrode system, sulfuric acid solution is used as the electrolyte and cyclic voltammetry is used to activate the hydrophilic carbon paper to obtain a carbon paper carrier.
[0029] Specifically: The three-electrode system is mainly composed of: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, carbon paper as working electrode, and 0.45~0.55 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as: the upper limit of potential is 0 V, the lower limit is -1.7 V~-2.3V, the starting potential is 0 V, the number of cycles is 6~8 times, and the scanning speed is 90~110 mV / s.
[0030] In S2 of the present invention, the copper catalyst is grown on the carbon paper carrier by electrodeposition, which specifically comprises the following steps: (1) Prepare the electrolyte using copper nitrate, concentrated sulfuric acid and citric acid as precursors.
[0031] Specifically: in the electrolyte, the concentration of copper nitrate is 0.005-0.05 mol / L, more preferably 0.01 mol / L; the concentration of citric acid is 0.01-0.1 mol / L, preferably 0.04-0.06 mol / L, more preferably 0.05 mol / L; the solution mixing and stirring time is 25-35 min, and the pH of the electrolyte is 1-4, preferably pH 4.
[0032] (2) The copper catalyst was grown on a carbon paper support using the chronoamperometry method.
[0033] Specifically, the electrolyte of step (1) is used as the electrolyte, the carbon paper support is used as the working electrode, the Pt sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, a potential of -1.0 to -1.4 V is applied, and the electrodeposition is performed. The electrodeposition time is 100 to 500 s, more preferably 250 to 350 s, and the electrodeposition temperature is 20 to 30 °C.
[0034] The washing in S3 of the present invention is specifically rinsing with running clean water for 45 to 75 seconds; the drying temperature is 55 to 65° C. and the drying time is 16 to 24 hours.
[0035] The preparation method of the metal copper catalyst of the present invention uses citric acid as a complexing agent to arrange Cu atoms along a direction with lower energy, thereby forming a metal copper catalyst with abundant (110) crystal planes. During electrocatalytic CO2 reduction, compared with the simple (100) crystal plane, a rapid CC coupling process can occur on the (110) crystal plane to promote the generation of C2 products. At the same time, compared with the (111) crystal plane, the removal process of H2O during the catalytic process on the (110) crystal plane is suppressed, so the selectivity of the ethanol product on the (110) crystal plane is significantly improved. In addition, citric acid forms a stable complex with copper nitrate, which also improves the stability of the electrolyte and ensures the smooth progress of the electrodeposition process. Adding an appropriate amount of sulfuric acid can improve the conductivity of the electrolyte.
[0036] The metallic copper catalyst obtained by the preparation method of the present invention is composed only of copper. When the electrodeposition time is controlled to be 300s, the catalyst exhibits a unique hexagonal tower structure, which is formed by stacking a large number of alternately grown (100) and (111) crystal planes, and forming abundant (110) crystal planes at the interface of the two crystal planes. The catalyst of the present invention has excellent selectivity for ethanol products in the electrocatalytic CO2 reduction reaction, and the selectivity for ethanol products is 46.2-78.9% Faraday efficiency.
[0037] Example 1 The hexagonal Cu-N-300 catalyst is prepared according to the preparation method proposed by the present invention: (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0038] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0039] (3) Add copper nitrate, citric acid and concentrated sulfuric acid to 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.01 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.05 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0040] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V for 300 s using a constant voltage to obtain a Cu catalyst supported on the carbon paper. (5) The sample after electrodeposition was taken out and rinsed with running water for 1 min to obtain the catalyst material Cu-N-300 that can be used for electrocatalytic reaction.
[0041] The catalyst morphology obtained in this example 1 is as follows Figure 1 As shown in a, the Faraday efficiency of the product of the electrocatalytic CO2 reduction reaction of the catalyst at different overpotentials is shown in Figure 5 As shown in a in the figure, the Faraday efficiency of ethanol in the electrocatalytic CO2 reduction reaction can reach up to 79.8%.
[0042] Example 2 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0043] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0044] (3) Add copper nitrate, citric acid and concentrated sulfuric acid to 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.01 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.05 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0045] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 100 s to obtain a Cu catalyst supported on the carbon paper. (5) The sample after electrodeposition was taken out and rinsed with running water for 1 min to obtain the catalyst material Cu-N-100 that can be used for electrocatalytic reaction.
[0046] The catalyst Cu-N-100 obtained in Example 2 has a Faradaic efficiency of 46.2% for ethanol in the electrocatalytic CO2 reduction reaction.
[0047] Example 3 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0048] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0049] (3) Add copper nitrate, citric acid and concentrated sulfuric acid to 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.01 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.05 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0050] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 500 s to obtain a Cu catalyst supported on the carbon paper. (5) The sample after electrodeposition was taken out and rinsed with running water for 1 min to obtain the catalyst material Cu-N-500 that can be used for electrocatalytic reaction.
[0051] The catalyst Cu-N-500 obtained in this example has a Faradaic efficiency of 57.5% for ethanol in the electrocatalytic CO2 reduction reaction.
[0052] Example 4 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0053] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0054] (3) Add copper nitrate, citric acid and concentrated sulfuric acid into 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are 0.01 mol / L copper nitrate, 0.1 mol / L sulfuric acid and 0.05 mol / L citric acid. Stir the above components in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 1.
[0055] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i4 .
[0056] Figure 6 The scanning electron microscopy results in (a) show that the Cu catalyst obtained under the conditions of this example mainly exhibits the morphology of nanoparticles.
[0057] Example 5 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0058] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0059] (3) Add copper nitrate, citric acid and concentrated sulfuric acid into 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are 0.01 mol / L copper nitrate, 0.005 mol / L sulfuric acid and 0.05 mol / L citric acid. Stir the above components in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 2.
[0060] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i5 .
[0061] Figure 6 The scanning electron microscopy results in (b) show that the Cu catalyst obtained under the conditions of this example mainly exhibits agglomerated blocks.
[0062] Example 6 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0063] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0064] (3) Add copper nitrate, citric acid and concentrated sulfuric acid into 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.01 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.01 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0065] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i6 .
[0066] Figure 6 The scanning electron microscopy results in (c) show that the Cu catalyst obtained under the conditions of this example mainly exhibits the morphology of random nanosheets.
[0067] Example 7 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0068] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0069] (3) Add copper nitrate, citric acid and concentrated sulfuric acid to 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.01 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.1 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0070] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i7 .
[0071] Figure 6 The scanning electron microscopy results in (d) show that the Cu catalyst obtained under the conditions of this example mainly exhibits the morphology of randomly aggregated nanosheets.
[0072] Example 8 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0073] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0074] (3) Add copper nitrate, citric acid and concentrated sulfuric acid into 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.005 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.05 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0075] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i8 .
[0076] Figure 6 The scanning electron microscopy results in (e) show that the Cu catalyst obtained under the conditions of this example not only presents a regular hexagonal structure but also has a large number of nanoparticles.
[0077] Example 9 (1) 1×1.5 cm carbon paper was ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min respectively, and then treated with 1 mol / L sulfuric acid at 60 °C for 60 min to obtain hydrophilic carbon paper.
[0078] (2) The hydrophilic carbon paper was activated by cyclic voltammetry in a three-electrode system to obtain a carbon paper carrier: the composition of the three-electrode system is: Pt sheet as counter electrode, Ag / AgCl electrode as reference electrode, hydrophilic carbon paper as working electrode, and 0.5 mol / L sulfuric acid solution as electrolyte; the cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -2.0 V, the starting potential is 0 V, the number of cycles is 7 times, and the scanning speed is 100 mV / s.
[0079] (3) Add copper nitrate, citric acid and concentrated sulfuric acid into 30 mL of water to prepare an electrolyte. The concentrations of the different substances in the electrolyte are: 0.05 mol / L copper nitrate, 1 mol / L sulfuric acid and 0.01 mol / L citric acid. The above components are stirred in water for 30 min until they are completely dissolved to obtain an electrolyte. The pH value of the electrolyte is 4.
[0080] (4) Using the carbon paper support obtained in step (2) as the working electrode, the Pt sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electrolyte obtained in step (3) at a potential of -1.2 V using a constant voltage deposition for 300 s to obtain a Cu catalyst supported on the carbon paper. (5) Take out the electrodeposited sample and rinse it with running water for 1 min to obtain the catalyst material Cu-N i9 .
[0081] Figure 6 The scanning electron microscopy results in (f) show that the Cu catalyst obtained under the conditions of this example exhibits a large number of assembled pine cone structures.
[0082] Comparative Example 1 The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that copper nitrate is replaced by copper chloride to prepare a Cu-C catalyst.
[0083] The morphology and structure of the obtained Cu-C catalyst are as follows: Figure 1 As shown in (b), the catalyst has a Faradaic efficiency of 38.8% for ethanol in the electrocatalytic CO2 reduction reaction.
[0084] Comparative Example 2 The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that copper nitrate is replaced by copper sulfate to prepare a Cu-S catalyst.
[0085] The morphology and structure of the obtained Cu-S catalyst are as follows: Figure 1 As shown in Figure c, the catalyst has a Faradaic efficiency of 20.3% for ethanol in the electrocatalytic CO2 reduction reaction.
[0086] Comparative Example 3 The preparation method of Comparative Example 3 is basically the same as that of Example 1, except that unactivated carbon paper is used as a carrier for electrodeposition. Experiments have shown that unactivated carbon paper exhibits hydrophobicity and Cu catalyst cannot be grown by electrodeposition.
[0087] Comparative Example 4 The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that carbon paper activated by sulfuric acid alone is used as a carrier for electrodeposition to prepare Cu-N c4 catalyst.
[0088] Comparative Example 5 The preparation method of Comparative Example 5 is basically the same as that of Example 1, except that: carbon paper activated by electrochemical method is used as a carrier for electrodeposition to prepare Cu-N c5 catalyst.
[0089] Comparative Example 6 The preparation method of Comparative Example 6 is basically the same as that of Example 1, except that the carbon paper is replaced with copper foil as a carrier for electrodeposition to prepare Cu-N c6 catalyst.
[0090] Comparative Example 7 The preparation method of Comparative Example 7 is basically the same as that of Example 1, except that citric acid is replaced by tannic acid for electrodeposition to prepare Cu-N c7 catalyst.
[0091] like Figure 1 As shown, a, b, and c are scanning electron microscope images of the catalysts prepared in Example 1, Comparative Example 1, and Comparative Example 2, respectively. Figure 1It can be seen that when different copper sources are used for electrodeposition, only the copper nitrate precursor can induce the formation of a hexagonal pyramid structure. In comparison, when copper sulfate is used as a precursor, the resulting catalyst mainly presents a flake structure, while when copper chloride is used as a precursor, the resulting catalyst is a stacked nano-dendritic structure.
[0092] Figure 2 The scanning electron microscope images of the catalysts prepared in Examples 2 and 3 are shown. Figure 2 It can be seen that the evolution process of the hexagonal tower-like structure is closely related to the electrodeposition time. When the deposition time is short, the catalyst is mainly irregular polygonal nanoparticles, while when the deposition time is long, the stacked hexagonal tower-like structures are further assembled to form a three-dimensional structure similar to a pine cone.
[0093] Figure 3 The high-resolution atomic arrangement of the catalyst prepared in Example 1 is shown. Figure 3 It can be seen that the hexagonal pyramid structure obtained in Example 1 exposes a large number of (111) and (100) crystal planes, and a large number of (110) crystal planes are formed on the interface between the two crystal planes. Figure 4 From the analysis, it can be seen that the catalyst Cu-N-300 prepared in Example 1 and the catalysts in Comparative Examples 1 and 2 are mainly single copper, and a small amount of Cu2O is generated on the catalyst surface. Figure 5 It can be seen that the crystal plane ratios of the catalysts obtained under different precursor types and different electrodeposition times are significantly different. Since the (110) and (100) crystal planes of Cu cannot be directly displayed on XRD, they are represented by the corresponding (220) and (200) crystal planes. Figure 5 It can be seen that the (110) crystal plane ratio of the catalyst Cu-N-300 of Example 1 is higher than that of the catalysts of Comparative Examples 1 and 2; the (110) crystal plane ratio of the catalyst Cu-N-300 of Example 1 is higher than that of Examples 2 and 3. The above analysis results show that the type of precursor and the electrodeposition time will not only affect the crystal plane composition of the Cu catalyst, but also affect the morphology of the catalyst and the geometric relationship between different crystal planes.
[0094] Figure 6 The catalyst morphology obtained under different electrolyte conditions. i4 and Cu-N i5It can be seen that the concentration of sulfuric acid not only affects the pH of the electrolyte, but also affects the deposition and growth behavior of Cu. When the concentration of sulfuric acid is 0.1 mol / L, large cracks appear on the surface of the carbon paper and the deposition uniformity decreases. When the concentration of sulfuric acid is 0.005 mol / L, the sample shows a large-area aggregation state. i6 and Cu-N i7 It can be seen that when the concentration of citric acid is too low or too high, the sample presents a tortoise-like nanosheet or aggregate state. i8 and Cu-N i9 It can be seen that when the copper nitrate concentration is too low, a large number of unassembled nanoparticles appear in the sample, while a high concentration of copper nitrate will lead to the appearance of a pine cone-like structure formed by large-scale excessive self-assembly. c4 and Cu-N c5 It can be seen that almost no Cu catalyst deposition can be found on the carbon paper activated by only one method. Figure 7 It can be seen from the results that from the scanning electron micrograph of the catalyst of Comparative Example 3, copper catalyst cannot be produced on unactivated carbon paper (a); when copper foil is used as a carrier, a self-assembled hexagonal tower structure cannot be obtained (b); when tannic acid is used as a complexing agent, the sample presents an irregular nanosphere structure (c).
[0095] The electrocatalytic CO2 performance of the catalyst was tested using a three-electrode system in the Chenhua electrochemical workstation. Carbon paper loaded with Cu catalyst was used as the working electrode, Pt sheet as the counter electrode, Hg / HgO electrode as the reference electrode, and 1M KHCO3 solution as the electrolyte. Before the reaction, CO2 was introduced into the electrode solution at a flow rate of 100 mL / min for 30 min to saturate it. During the reaction, CO2 was continuously introduced into the system at a flow rate of 6 mL / min, and the reaction was carried out at a certain potential for 3 hours. After the reaction, the liquid and gas products were collected separately, and their components were detected by chromatography. CO and CH4 in the gas products were detected by TCD, H2 was detected by FID1, and the liquid products were detected by FID2 detector equipped with a liquor column.
[0096] The product distributions of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 at different potentials are shown in FIG. Figure 8 As shown, the product distribution of all catalysts at -0.215 V is as follows Fig. 9As shown. By comparing the experimental results of Comparative Examples 1 and 2 with those of Example 1, it can be found that when copper nitrate is used as a precursor, the selectivity of the obtained copper catalyst for ethanol products is better than that of copper sulfate and copper chloride precursors. At the same time, by comparing the results of Examples 1 to 3, it can be seen that when the catalyst forms a regular hexagonal tower structure, the selectivity of the catalyst for ethanol products is optimal. This is because in the formed hexagonal tower structure, the alternating exposure of the (100) and (111) crystal planes generates abundant (110) crystal planes in the catalyst. Compared with the (100) crystal plane and the (111) crystal plane, the (110) crystal plane formed on the (100) and (111) interfaces is conducive to CC coupling and can inhibit the dehydration process to a certain extent, thereby significantly improving the production process of C2 product ethanol. Fig.10 This is a test diagram of the electrocatalytic CO2 reduction cycle stability of the catalyst Cu-N-300 in Example 1. Fig.10 It can be seen that the catalyst Cu-N-300 showed good stability in the CO2 reduction test lasting up to 18 h.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a metallic copper catalyst, characterized in that: include: S1, hydrophilic modification and activation of carbon paper to obtain a carbon paper carrier; S2, using a mixture of copper nitrate, sulfuric acid, citric acid and water as the electrolyte, the copper catalyst was grown on the carbon paper support by electrodeposition; S3, washing and drying the carbon paper carrier on which the copper catalyst is grown, to obtain a metallic copper catalyst supported on the carbon paper carrier.
2. The method for preparing a metallic copper catalyst according to claim 1, characterized in that: S1 specifically includes: (1) The carbon paper is washed with deionized water and anhydrous ethanol to remove impurities, then added into a sulfuric acid solution and heated to obtain a hydrophilic carbon paper; (2) In a three-electrode system, sulfuric acid solution is used as the electrolyte and cyclic voltammetry is used to activate the hydrophilic carbon paper to obtain a carbon paper carrier.
3. The method for preparing a metallic copper catalyst according to claim 2, characterized in that: In step (1), the heating temperature is 50-70°C and the heating time is 50-70 min.
4. The method for preparing a metallic copper catalyst according to claim 2, characterized in that: In step (2), the three-electrode system uses a Pt sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and a hydrophilic carbon paper as a working electrode. The cyclic voltammetry parameters are set as follows: the upper limit of the potential is 0 V, the lower limit is -1.7 V to -2.3 V, the starting potential is 0 V, the number of cycles is 6 to 8 times, and the scanning speed is 90 to 110 mV / s.
5. The method for preparing a metallic copper catalyst according to claim 1, characterized in that: In S2, in the electrolyte, the concentration of copper nitrate is 0.005-0.05 mol / L, and the concentration of citric acid is 0.01-0.1 mol / L.
6. The method for preparing a metallic copper catalyst according to claim 1, characterized in that: In S2, the pH value of the electrolyte is 1~4.
7. The method for preparing a metallic copper catalyst according to claim 1, characterized in that: In S2, the electrodeposition time is 100~500 s.
8. The method for preparing a metallic copper catalyst according to claim 1, characterized in that: In S2, the potential applied by the electrodeposition method was -1.0~-1.4 V.
9. A metallic copper catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the metallic copper catalyst according to claim 9 in electrocatalytic CO2 reduction.
Citation Information
Patent Citations
Preparation method of Cu-P-100 catalyst and application of Cu-P-100 catalyst in carbon dioxide electrocatalytic reduction
CN114134530A
In-situ preparation method of catalyst for electrocatalytic reduction of CO2
CN116905040A
Electrode loaded with copper nano beam catalyst as well as preparation method and application of electrode
CN117210851A
Clit pedal for preventing falling
KR1020250084786A